Characteristics of Influencer Relations: A Literature Review - Theresia Lavietha Vivrie Lolita (Jurnal Ilmu Komunikasi, 2022)
Ensuring a collaboration in influencer relations remains authentic, organic, and transparent remains a tricky compensating act and can be challenging for many companies and influencers to keep up though influencer relations have existed for a long time. This research aims at providing an exhaustive summary of the literature relevant to the characteristics of influencer relations. This study conducted a narrative literature review on influencer relationships which have features: 1) The communication aim is primarily at the opinion market and directly influencing the formation of opinions; 2) The goals usually are image and reputation enhancement, information and knowledge transfer; 3) Credibility and transparency of communication are crucial for achieving the goal; 4) Evaluation using image and reputation indicators, interactions, and sentiment analysis. This study suggests that strategic approaches focus on influencer relationships that spotlight authenticity to bring organizations accomplishment in influencer partnership. The research recommends the stages of corporate public relations to maintain authentic influencer relationships in adapting to the ever-changing communication landscape.